Contact potential and scanning Kelvin force microscopy measurements on sulphate-anion intercalated graphite. (20th March 2018) - Yivlialin, R.; Pace, G.; Bussetti, G.; Caironi, M.; Duò, L.
Abstract: In the current interpretative model of graphite anion intercalation, the characteristic blisters, formed after the incipient surface oxidation, have the same structural behaviour of pristine graphite. However, this result is deduced from scanning tunneling microscopy data, which cannot give a chemical fingerprint of the electrode surface. Conversely, the contact potential difference between a reference tip and a sample depends on the chemical as well as on the structural conditions of the surface. As a consequence, in this paper, we combine a contact potential measurement with a scanning Kelvin force microscopy analysis, in order to extract information on electronic changes occurring to the electrode with a sub-micrometre investigation of the surface morphology after the incipient graphite oxidation process in diluted sulphuric acid. The results suggest that, as well as the structural properties, no significant electronic differences occur between blisters and the graphite basal plane after the intercalation process.